The mythological genesis of the pre-socratic logos: conceptual similarities between cosmogonic poetry and natural philosophy - Costa de Freitas, Jan Clefferson (Trilhas Filosóficas, 2025)
In this article we present an analysis and description of the interconnections between Greek poetry and the emergence of pre-Socratic thought, highlighting the conceptual affinities that link mythical imaginary to rational reflection. It is argued that the natural philosophy of the originary thinkers did not emerge in isolation from history, culture and society, but as an innovative interpretation of pre-existing concepts in mythological narratives. Through an analytical-descriptive methodology that combines bibliographical review, hyperfocused reading, comparative studies, hermeneutic proficiency, critical approach and creative writing, this work aims to demonstrate that pre-Socratic rationality did not entirely break with the word of the poets, but was a way of interpreting the world that drew inspiration from the primordial sources of mythology. Thales, Anaximander and Anaximenes will be thought of here from connections with the poetics of Homer and Hesiod, in order to reveal how mythical language was transformed into an instrument for understanding nature and the universe. As a result of this philosophical investigation, we intend to elucidate the extent to which the emergence of Logos is intrinsically linked to Mythos, suggesting that the difference between the two categories is not an opposition, but a dialectical continuity.